Conflict in resource management for ecosystem services: water in Lashi watershed, Lijiang - Yu Xiaogang (2001)
This article discusses the role of forests at different elevations in providing ecosystem services, and particularly water. It analyses the changes in forest management and their consequences over the post liberation period, concentrating on the post-1983 devolution of forest management to village and household levels. A more detailed description of the forestry situation in three villages, Nanyao and western and eastern villages is presented. Following this, the effects of various forest management systems, including the various forms of local forest management on the provision of ecosystem services are considered. A discussion of various forms of inequality embodied in the tree extraction of external ecosystem services, the inequalities being those between the town and countryside, between lowland and upland and between men and women. The ways in which a market for the ecosystem product, water could be established are considered along with the implications of such a market for local communities.